2010
DOI: 10.1002/pon.1703
|View full text |Cite
|
Sign up to set email alerts
|

Objective burden, resources, and other stressors among informal cancer caregivers: a hidden quality issue?

Abstract: A great deal of clinical cancer care is delivered in the home by informal caregivers (e.g. family, friends), who are often untrained. Caregivers' context varies widely, with many providing care despite low levels of resources and high levels of additional demands. Background Changes in health care have shifted much cancer care to the home, with limited data to inform this transition. We studied the characteristics, care tasks, and needs of informal caregivers of cancer patients. Methods Caregivers of seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
217
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(229 citation statements)
references
References 37 publications
8
217
0
4
Order By: Relevance
“…Caregiver activities, roles, and demands during posttreatment depend on the residual impact and the treatment the patient has received as well as the long-term expectation of survival and outcome of treatment (13,14,(20)(21)(22). From our work, we have found that 60% of 143 patients who were from 2 to 6 weeks posttreatment reported substantial problems (23).…”
Section: Transition For Patients and Caregivers Posttreatmentmentioning
confidence: 82%
See 2 more Smart Citations
“…Caregiver activities, roles, and demands during posttreatment depend on the residual impact and the treatment the patient has received as well as the long-term expectation of survival and outcome of treatment (13,14,(20)(21)(22). From our work, we have found that 60% of 143 patients who were from 2 to 6 weeks posttreatment reported substantial problems (23).…”
Section: Transition For Patients and Caregivers Posttreatmentmentioning
confidence: 82%
“…The need for caregiver involvement following active patient treatment may continue for several years, as patients have residual symptoms, late effects, and disability (13,14,19). Caregiver activities, roles, and demands during posttreatment depend on the residual impact and the treatment the patient has received as well as the long-term expectation of survival and outcome of treatment (13,14,(20)(21)(22).…”
Section: Transition For Patients and Caregivers Posttreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…El algoritmo recomienda la utilización de alguno de los siguientes instrumentos al evaluar sintomatología depresiva: Escala de Depresión del Centro de Estudios Epidemiológicos (CES-D) (>16) (26,27) Inventario de depresión de Beck (BDI) (mínima 0-9, leve 10-16, moderada 17-29 y severa 30-63) (28,29) . Ansiedad: Inventario de ansiedad: rasgo-estado (IDARE): estado (mínima 36-44, leve 45-52, moderada 53-61 y severa 62-79), rasgo (mínima 23-31, leve 32-37, moderada 38-43 y severa 44-68) (30,31) .…”
Section: Evaluaciónunclassified
“…7 Poor communication between clinicians and patients and their families can have significant negative consequences, including less patient or family satisfaction with cancer care, 8,9 less trust in physicians, 10 fear of being abandoned, 11,12 poorer pain control, 13 feelings of hopelessness, 14 caregiver burden, 15,16 less commitment to treatment decisions, 17 lower rates of cancer screening, 18 and disparities in cancer care. 19,20 Given the importance of PCC in improving cancer care quality and outcomes, there is a need for systematic assessment of patients' communication experiences when receiving cancer-related health care.…”
mentioning
confidence: 99%